Endoscopic resection for gastric subepithelial tumours: a retrospective cohort study - Ji Li; Dong Xu; Weifeng Huang; Xiaoyi Lei; Yanqing Wang; Jinyan Zhang (Annals of Medicine)
Objective Although endoscopic resection (ER) is an established technique for gastric subepithelial tumours (SETs), comprehensive data on its efficacy and safety remain limited. This study aimed to evaluate the efficacy and safety of ER in patients with gastric SETs and to identify risk factors associated with procedure-related complications.Materials and methods This retrospective study included 483 patients who underwent ER for gastric SETs between February 2012 and May 2023. Patient demographics, tumour characteristics, and clinical outcomes were evaluated. Multivariate analysis was performed to identify risk factors for complications.Results The median tumour size was 1.2 cm (range: 0.5–6.0 cm). The complete resection rate was 93.8%. Complications occurred in 6.8% of cases, including perioperative bleeding (2.1%), perforation (1.7%), and both (0.4%), with 0.8% of cases requiring conversion to surgery. Larger tumours notably increased the risks of incomplete resection (odds ratio [OR] = 1.605, 95% confidence interval [CI]: 1.066–2.416, p = 0.023), perioperative bleeding (OR = 2.004, 95% CI: 1.099–3.653, p = 0.023), and perforation (OR = 3.476, 95% CI: 1.830–6.602, p < 0.001). Additionally, an irregular tumour shape significantly elevated the risk of incomplete resection (OR = 10.771, 95% CI: 3.452–33.605, p < 0.001). Conversely, tumours located in the middle third (OR = 0.068, 95% CI: 0.014–0.341, p = 0.001) and the upper third (OR = 0.211, 95% CI: 0.051–0.884, p = 0.033) of the stomach substantially reduced the risk of incomplete resection.Conclusions ER is an effective and generally safe treatment modality for managing gastric SETs. However, larger tumour size and irregular shape are significant risk factors for adverse outcomes.